Plastic occurrence, sources, and impacts in Antarctic environment and biota - Caruso, Gabriella; Bergami, Elisa; Singh, Neelu; Corsi, Ilaria (Water Biology and Security, 2022)
Several studies have documented that plastic pollution is affecting one of the most remote and pristine regions of our planet, Antarctica. Plastics of different size and polymeric composition have been retrieved in Antarctic sea ice, surface waters and sediments, with microplastics (mostly fibers) found both in terrestrial and marine organisms. Such evidence raises concerns about potential detrimental effects on biodiversity and ecosystem functions. The present review aims to report the most up-to-date knowledge on occurrence and distribution of plastic pollution in the Antarctic environment and biota including interaction with microorganisms, potential sources, and its impact on Antarctic biota. Our understanding of plastic pollution in this polar region will help us define the human footprint in Antarctica and predict future ecological risks.
Keywords: Sørishavet; forurensning; plastpartikler; økotoksikologi